2017
DOI: 10.1016/j.tins.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Revolution of Resting-State Functional Neuroimaging Genetics in Alzheimer’s Disease

Abstract: The quest to comprehend genetic, biological, and symptomatic heterogeneity underlying Alzheimer’s disease (AD) requires a deep understanding of mechanisms affecting complex brain systems. Neuroimaging genetics is an emerging field that provides a powerful way to analyze and characterize intermediate biological phenotypes of AD. Here, we describe recent studies showing the differential effect of genetic risk factors for AD on brain functional connectivity in cognitively normal, preclinical, prodromal, and AD de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 85 publications
3
23
0
Order By: Relevance
“…Therefore, basal forebrain functional alterations may be a promising candidate for an early preclinical biomarker of AD and a potentially useful functional outcome in of both factors: the APOE ´4 allele showed stronger correlation between the global brain amyloid deposit and the PBF functional dynamics in occipital regions and in the thalamus. We provided further evidence that the APOE ´4 allele is linked to abnormal amyloid-b aggregation (41)(42)(43)(44) and leads to differences in the brain functional organization in cognitively intact individuals (2). This result supports the hypothesis of different binding characteristics of the APOE ´4 isoform with amyloid-b (45).…”
Section: Role Of Apoe Genotype and Sex On The Basal Forebrain Rsfc-susupporting
confidence: 81%
“…Therefore, basal forebrain functional alterations may be a promising candidate for an early preclinical biomarker of AD and a potentially useful functional outcome in of both factors: the APOE ´4 allele showed stronger correlation between the global brain amyloid deposit and the PBF functional dynamics in occipital regions and in the thalamus. We provided further evidence that the APOE ´4 allele is linked to abnormal amyloid-b aggregation (41)(42)(43)(44) and leads to differences in the brain functional organization in cognitively intact individuals (2). This result supports the hypothesis of different binding characteristics of the APOE ´4 isoform with amyloid-b (45).…”
Section: Role Of Apoe Genotype and Sex On The Basal Forebrain Rsfc-susupporting
confidence: 81%
“…Our findings of the different effects of APP and PS1 mutation on this circuit expanded our understanding of this potential biomarker. Both APP and PS1 mutation can cause direct elevation of the Aβ level via alterations of their encoding proteins and, as a result, affect synaptic plasticity [40,63]. They also affect other functions of their encoding proteins, such as axonal transport, lysosome PS1 and APP mutation subjects without symptoms were compared with the control group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most of the above imaging findings in FAD have involved mutation carriers of various genes, while not looked at the effect of specific gene. Imaging studies have shown gene-or mutation-specific effect on brain structure [38,39] and function [40] in Alzheimer's disease, but the gene-specific effect on the frontostriatal and hippocampus-PCC neural circuits remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, several potential biological markers have been identified across the full spectrum of AD, from preclinical to prodromal to clinical stages [3541]. This includes different categories, as follows: 1) neurogenetics/neuroepigenetics markers [4245], 2) neurochemistry markers [4, 4648], including both cerebrospinal fluid (CSF) [4955] and blood (plasma/serum) markers [5663], 3) markers derived from structural/functional/metabolic neuroimaging [6468], and 4) neurophysiology/neurodynamic markers [69]. Moreover, opinions of regulatory agencies and industry stakeholders in AD biomarker discovery area are regularly in discussion and development [70, 71].…”
Section: The Precision Neurology Paradigm In Alzheimer’s Diseasementioning
confidence: 99%
“…The tailoring of therapeutics could benefit from associations between biomarkers and the presence of the disease pathophysiology. Given the variability that is present in AD patients and MCI subjects, the ICN-based biomarkers and their relation to genetic profiles [68] may be able to provide an improved systems biology characterization of brain function. The use of ICNs for tailoring therapeutics still needs considerable development work, and there is currently only limited work on the effects of an AD-related drug on ICNs [307].…”
Section: Contribution and Role Of Functional Magnetic Resonance Imagimentioning
confidence: 99%